BOARD DIVERSITY NETWORKS AND EARNINGS QUALITY IN MALAYSIA - Mohd Faizal Jamaludin; Fathyah Hashim, (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study examines the relationship between board diversity networks and earnings quality using different direct and indirect network centrality measures established by social network analysis. This study establishes the network pattern of 4416 directors consists of 4609 men and 407 women directors from a sample of 745 listed companies on Bursa Malaysia in 2011. Overall, the results show that there is a significant negative relationship between director networks and earnings quality. Additionally, the analysis on gender-based networks suggests that while the effect of men directors’ networks is consistent with the main network model, the women directors create a network which capable of enhancing the company’s earnings quality. The negative network effects on earnings quality most likely due to the reputation of social status, which eventually detriment the companies’ value.